Stakeholders’ perceptions about a surgical site infection master training plan for a low-middle income country - Khan, Muhammad Nasir Ayub; Mook, Walther Nicolaas Anton van; Bhatti, Abu Baker Hafeez; Dolmans, Diana H.J.M.; Verstegen, Daniëlle M.L. (International Journal of Infection Control, 2023)
Background: Training is a critical component for improving the practice of surgical site infections (SSI). We have designed a master training plan characterized by a task-based, interprofessional and reflective approach consisting of initial training of employees and subsequent refresher training. It aims to improve the practice of SSI in hospitals. The research question was: How do policymakers, teachers and managers/leaders of health care institutions perceive the outline of a master training plan for SSI? Methods: Semi-structured interviews were conducted with a purposive sample of 28 stakeholders from three categories. Results: Four key themes emerged from the interviews: 1) Discussion of authentic tasks fosters the transfer of knowledge to the workplace; 2) interprofessional reflective learning comes with challenges; 3) the master training plan help to change behavior, and 4) it is feasible with limited resources. However, the stakeholders pointed that interprofessional training creates friction among health care professionals (HCPs) who work together and participate in the interprofessional training sessions. To disseminate the training across healthcare facilities, stakeholders suggested developing a train-the-trainer plan. Furthermore, stakeholders suggested making HCPs accountable for actual behavior changes in the workplace. Conclusion: The stakeholders agreed with the approach that the master plan is based on. Implementing this master training plan was expected to encourage knowledge and skills to practice. Participants indicated that arranging training might be feasible in different institutions and it should be part of undergraduate, postgraduate, and continuing medical education. The stakeholders perceived the outline of the master training plan to be well-suited for implementation in low- and middle-income countries (LMICs).